Impact of rotavirus vaccine introduction in Abidjan, Côte d'Ivoire. Issue 1 (31st December 2023) - Britoh Mlan, Alice; Burke, Rachel M.; Koné, Hamidou; Boni-Cisse, Catherine; N'Guessan, Rebecca; Zaba, Flore; Aka, Lepri Nicaise; N'Zue, Kofi; Adom, San Koffi; Kouadio, Sié Kabran; Bhérat Kouadio, Armel; Meité, Syndou; et al.
ABSTRACT: Côte d'Ivoire introduced rotavirus vaccine in March 2017. Rotavirus surveillance is conducted at Centre Hospitalier Universitaire de Yopougon in Abidjan, the capital city. Children <5 years of age are enrolled in rotavirus surveillance if admitted to the hospital with acute gastroenteritis. We used sentinel surveillance data from 2014 through mid-2019 to compare trends in rotavirus pediatric gastroenteritis hospitalizations before and after rotavirus vaccine introduction. We used Poisson regression to analyze changes in rotavirus prevalence, adjusting for calendar month and accounting for total monthly admissions; January 2014 – December 2016 was considered "pre-vaccine, " and January 2017 – June 2019 was considered "post-vaccine." Age distribution and severity were compared between periods using the Mann-Whitney U test. Rotavirus-positive admissions declined 51% (95% CI: 28%-67%), from 31.5% pre-vaccine to 14.9% afterward. The median age of rotavirus-positive children increased from 7 months (interquartile range [IQR]: 5–11) in the pre-vaccine period to 11 months (IQR: 7–18, p  = .005) in the post-vaccine period. The median severity score decreased from 11 to 9 ( p  = .008) among all children, and from 12 pre- to 10.5 post-vaccine ( p  = .35) among rotavirus-positive children. Our findings suggest that rotavirus vaccine introduction contributed to reduced rotavirus hospitalization in Abidjan and possibly more broadly.